2018
DOI: 10.1021/acs.chemrev.7b00731
|View full text |Cite
|
Sign up to set email alerts
|

Methods for 2-Deoxyglycoside Synthesis

Abstract: Deoxy-sugars often play a critical role in modulating the potency of many bioactive natural products. Accordingly, there has been sustained interest in methods for their synthesis over the past several decades. The focus of much of this work has been on developing new glycosylation reactions that permit the mild and selective construction of deoxyglycosides. This Review covers classical approaches to deoxyglycoside synthesis, as well as more recently developed chemistry that aims to control the selectivity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
175
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 268 publications
(188 citation statements)
references
References 414 publications
1
175
0
3
Order By: Relevance
“…[1] This important class of carbohydrates appears frequently in bioactive natural products, [2] but stereocontrolled glycosidic bond formation remains challenging. Inclusion of af unctional handle at C2 allows glycosylation to be influenced in atraceless fashion, rendering them ideal to access 2-deoxyglycosides.…”
mentioning
confidence: 99%
“…[1] This important class of carbohydrates appears frequently in bioactive natural products, [2] but stereocontrolled glycosidic bond formation remains challenging. Inclusion of af unctional handle at C2 allows glycosylation to be influenced in atraceless fashion, rendering them ideal to access 2-deoxyglycosides.…”
mentioning
confidence: 99%
“…[7,8] Thus,a2-deoxyglycosylation of the Asn residues could give the peptide chain stability against hydrolysis,r esulting in enhanced biological activity and selectivity [9] (Figure 1A). [12] Therefore,t he direct 2-deoxyglycosylation of hydroxyl groups [13,14] (Figure 1B,E q. [10,11] The direct 2-deoxyglycosylation of nucleophiles with glycals is one of the most straightforward approaches to 2-deoxysugar compounds.…”
mentioning
confidence: 99%
“…In this paper,wereport the first example of the direct 2-deoxyglycosylation of an amide group with our newly designed 2-halogenated azolium salts as Brønsted acids.The salient features of this method are as follows:1)the formation of the azolium salt enabled am ild condition, and [*] Y. Nakatsuji, Dr.Y . We initially investigated the reaction conditions used for the direct 2-deoxyglycosylation of hydroxyl groups, [12] and tested the ability of various acid catalysts to promote the 2deoxyglycosylation of amides with the typical galactal substrate 1 as am odel reaction (Table 1). [18] Furthermore,d uring the course of our investigations,i tw as found that the acid catalysts were inhibited by the amide groups.Detailed mechanistic investigations suggested that the halogen atom and the extended p-scaffold of our new catalyst played an important role for the improved catalytic activity, even in the presence of amides.…”
mentioning
confidence: 99%
See 2 more Smart Citations